Celiac Artery Stenting to Facilitate Hepatic Yttrium-90 Radioembolization Therapy. (6th December 2012) - Chamarthy, Murthy R.; Hughes, Terence W.; Gupta, Mohit; Vossen, Josephina A.; Velasco, Noel B.; Zinn, Kenneth M.
Abstract : Radioembolization offers a novel way to treat the nonresectable, liver predominant hepatic malignancies with better tumor response and overall progression-free survival rates. Transarterial catheter-based radioembolization procedure involves the hepatic arterial administration of glass- or resin-based beta emitting Yttirum-90 microspheres. Safe delivery of the tumoricidal radiation dose requires careful angiogram planning and coil embolization to quantify lung shunting and prevent systemic toxicity, respectively. Diagnostic pretreatment angiogram also serves to identify the hepatic arterial variant anatomy and other coexisting pathologies that might require a different or alternative approach. We describe a complex case of celiac artery stenosis with tortuous pancreaticoduodenal arterial arcade precluding access to the right hepatic artery for performing radioembolization. Celiac artery stenting of the stenosis was performed to facilitate subsequent safe and successful Yttrium-90 microsphere radioembolization.